ROOTING OF MINICUTTINGS AND MANAGED PRODUCTIVITY OF AUSTRALIAN CEDAR MINISTRAINS GROWN IN LIFTED SEEDBEDS AND TUBES - Mírian Peixoto Soares da Silva; Deborah Guerra Barroso; Juliana Sobreira de Souza; Daniele de Alvarenga Ferreira; José Geraldo de Araújo Carneiro (Ciência Florestal, 2012)
http://dx.doi.org/10.5902/198050987552 The planted forest stands aim to supply the growing demand for wood, especially for the sawing and veneer industries, that exclusively used wood from native forests. The Australian cedar (Toona ciliata) belongs to the family Meliaceae, is the species of interest for this sector. Studies with the Australian cedar propagation have carried out in latest years, mainly involving the use of mini-cuttings due to the need for high quality cuttings. The objectives of this paper were to evaluate the rooting and the productive capacity of Australian cedar mini-strains, managed in lifted seedbeds and 180 cm3 plastic tubes systems. So, two mini-clone                                                                      gardens were set up. The mini-strains of both gardens were grown from cut-off seedlings originated from seeds. Successive collections of sprouts were carried out to get the mini-cuttings. Afterwards, they remained in the rooting area under intermittent mist. Thirty days later the rooting characteristics of the cuttings originated from both mini-gardens were evaluated. The period of permanence of the cuttings in the gardens was seven-month long. During this period, six collections from the lifted seedbed and four from the plastic tubes were carried out. The mini-strains in the two systems showed 100% of survival rate. At the end of this seven-month period, an increasing tendency of the average number of mini-cutting was found out in both systems. Those from the lifted seedbed showed more productivity than those ones from the tubes. The plants from the mini-cuttings of the tube showed higher number and length of adventitious roots at the end rooting stage.